High-nickel ternary positive electrode material, preparation method thereof and lithium ion battery

By orientedly depositing Ti elements on the surface of high-nickel ternary positive electrode material to form a titanium-containing oxide modified layer and performing post-annealing treatment, the battery performance attenuation problem caused by the surface structure decay during the circulation process of the positive electrode material is solved, and higher cycling performance and rate performance are achieved, extending the cycle life of lithium-ion batteries.

CN119725438AActive Publication Date: 2025-03-28NANJING UNIV OF AERONAUTICS & ASTRONAUTICS
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411831398.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-03-28
Estimated Expiration
2044-12-12

AI Technical Summary

Technical Problem

The existing high-nickel ternary cathode materials have attenuated battery performance due to surface structure decay during circulation, and conventional processes cannot ensure the uniformity of the modified layer and the accuracy of the atomic doping amount, resulting in reduced material capacity and structural degradation.

Method used

The sol-gel method is used to deposit Ti elements on the substrate surface of the high-nickel layered positive electrode material to form a surface modification layer of titanium-containing oxides. The interdiffusion between the metal elements and the substrate surface elements is accelerated through post-annealing treatment, and the interfacial lattice oxygen stability is improved.

Benefits of technology

Effectively prevent direct contact between the positive electrode material and the electrolyte, reduce side reactions, prevent structural degradation, improve the circulation performance and rate performance of the material, and extend the circulation life of lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725438A_ABST
    Figure CN119725438A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of lithium ion batteries, and particularly relates to a high-nickel ternary positive electrode material, a preparation method thereof and a lithium ion battery. The high-nickel ternary positive electrode material comprises an inner core and a coating layer, the inner core is a ternary positive electrode material, and the coating layer comprises a titanium oxide compound. Metal ions in a coating layer introduced to the subsurface of the high-nickel layered positive electrode material can replace original metal ions in a matrix material, and the lattice oxygen structure stability can be effectively improved, so that the cycle performance and the thermal stability of the material are improved, and the cycle life and the safety performance of a lithium ion battery are further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium ion batteries, and in particular relates to a high-nickel ternary positive electrode material and a preparation method thereof, and a lithium ion battery. Background Art

[0002] Lithium-ion battery technology has been very mature and widely used in electric vehicles, energy storage, consumer electronics and other fields. Among the materials used in lithium-ion batteries, the performance of negative electrode materials such as graphite and silicon-carbon materials has basically reached the limit, and the cost is also relatively low, but there is still room for improvement in positive electrode materials. In order to obtain lithium-ion batteries with higher energy density, longer service life and safer, lithium-nickel mixing often occurs during the process of using ternary materials N. This is because Li + and Ni 4+ The atomic radius of the two materials is similar, so usually when producing high-nickel materials, excessive lithium salts are added to suppress the phenomenon of lithium-nickel mixing. However, the strong alkaline substances on the surface will further react with moisture and CO2 in the outside air during the preparation process, and finally transform into LiOH and Li2CO3, the main compounds of residual lithium on the surface. At the same time, the highly alkaline positive electrode material is easy to absorb moisture during the slurrying process, making the slurry become jelly-like, affecting the process of industrial production electrode preparation and increasing the cost of battery cell manufacturing.

[0003] To address these issues, materials can be modified from aspects such as material structure design, doping and coating. Surface coating modification is widely used due to its advantages such as low cost and high controllability. Surface treatment of high-nickel ternary cathode materials can improve the surface stability of cathode materials and effectively inhibit the side reactions between high-energy cathodes and organic electrolytes, becoming an important strategy and reliable way to regulate the surface interface of cathode materials.

[0004] The coating can effectively prevent the direct contact between the material and the electrolyte, and reduce the surface high activity Ni 4+ The side reaction between the surface and the electrolyte, and the elements introduced by surface doping can effectively inhibit oxygen precipitation, thereby inhibiting the degradation of the material surface from a layered structure to a defective spinel and a disordered rock salt structure, and improving the material's cycle performance: However, the coating and doping methods developed based on conventional dry and wet processes cannot guarantee the uniformity of the modified layer and the accuracy of the atomic doping amount. Therefore, the capacity of the modified material is usually reduced, and severe structural degradation and rapid capacity decay often occur after long cycles. Summary of the invention

[0005] In order to overcome the deficiencies in the prior art, the purpose of the present invention is to provide a high-nickel ternary positive electrode material and a preparation method thereof, and a lithium-ion battery, thereby improving the cycle life of the lithium-ion battery.

[0006] To solve the above problems, the technical solution adopted by the present invention is as follows:

[0007] A high-nickel ternary positive electrode material comprises a core and a coating layer, wherein the core is the ternary positive electrode material and the coating layer comprises a titanium oxide compound.

[0008] Preferably, the titanium oxide compound is TiO, TiO2, Ti2O3, Ti3O5, LiTiO2, Li2TiO3, Li4Ti5O 12 At least one of .

[0009] Preferably, the mass of the coating layer accounts for 0.01%-10% of the sum of the mass of the core and the coating layer. Further preferably, the mass of the coating layer accounts for 3% of the sum of the mass of the core and the coating layer.

[0010] A method for preparing a high-nickel ternary positive electrode material comprises the following steps:

[0011] 1) mixing a titanium source, hydrogen peroxide and ammonia in water to react to obtain a mixed reaction liquid; the titanium source is at least one of titanium propoxide, metatitanic acid, nano titanium nitride, titanium tetrachloride and tetrabutyl titanate;

[0012] 2) uniformly mixing the mixed reaction liquid obtained in step 1) with a mixed solvent to obtain a mixed liquid; the mixed solvent is obtained by mixing ethanol and water;

[0013] 3) adding the ternary positive electrode material to the mixed solution obtained in step 2), mixing evenly, and then treating at 25° C.-150° C. for 5-40 hours to obtain a powder;

[0014] 4) The powder obtained in step 3) is kept at 300-1000° C. for 3-10 hours under an inert atmosphere to obtain the product.

[0015] Preferably, the structural formula of the ternary cathode material in step 3) is LiNi x Co y Mn 1-x-y O2, 0.6≤x<1, 0 <y≤0.2,x+y<1。

[0016] Further preferably, the ternary positive electrode material is LiNi 0.6 Co 0.2 Mn 0.2 O2、LiNi 0.8 Co 0.1 Mn 0.1 O2 or LiNi 0.94 Co 0.03 Mn 0.03 O2.

[0017] Preferably, the ternary positive electrode material is a single crystal ternary positive electrode material or a polycrystalline ternary positive electrode material or a mixed material of a single crystal ternary positive electrode material and a polycrystalline ternary positive electrode material.

[0018] Preferably, the volume fraction of water in the mixed solvent in step 2) is 10%-50%.

[0019] Preferably, in step 1), the titanium source is mixed with hydrogen peroxide and ammonia in water to react by uniformly dispersing the titanium source in water, then adding hydrogen peroxide solution and ammonia solution, and mixing for 0.5-1h.

[0020] Further preferably, in step 1), 2-55 mL of hydrogen peroxide solution is used for every 67.4-1685 mg of the titanium source; the mass fraction of the hydrogen peroxide solution is 30%.

[0021] The treatment temperature in step 3) is preferably 75°C to 90°C, and the treatment time is 20h to 36h. More preferably, the treatment temperature is 85°C, and the treatment time is 24h.

[0022] Preferably, the insulation temperature in step 4) is 600-800° C., and more preferably the insulation time is 6-8 hours.

[0023] A lithium-ion battery comprises a positive electrode, a negative electrode, a separator and an electrolyte; the positive electrode comprises a positive electrode collector and a positive electrode material layer arranged on the positive electrode collector, the positive electrode material layer comprises a positive electrode active substance, and the positive electrode active substance is the above-mentioned high-nickel ternary positive electrode material or the high-nickel ternary positive electrode material prepared by the above-mentioned preparation method.

[0024] Beneficial effects of the present invention:

[0025] The present invention adopts a sol-gel method to directionally deposit Ti elements on the surface of a high-nickel layered positive electrode material substrate, controls the proportion of the coating layer and the spatial distribution in the high-nickel material by adjusting the content of the Ti element, controls the thickness of the modified layer by adjusting the temperature and time of recrystallization, and finally obtains a titanium oxide surface modified layer on the surface of the substrate material; and performs a post-annealing treatment on the modified high-nickel layered positive electrode material to accelerate the mutual diffusion of some metal elements in the titanium oxide surface modified layer and the surface elements of the high-nickel layered positive electrode material substrate, thereby improving the lattice oxygen stability at the interface between the substrate and the modified layer.

[0026] The present invention mainly investigates the influence of the titanium oxide surface modification layer on the electrochemical properties of the high-nickel layered positive electrode material; the focus is on solving the battery performance degradation caused by the surface structure degradation during the cycle of the high-nickel layered positive electrode material; the difficulty lies in the precise control of the thickness and uniformity of the titanium oxide surface modification layer, and the use of recrystallization technology allows the titanium oxide surface modification layer to spontaneously grow on the positive electrode material, thereby making the coating layer of the high-nickel layered positive electrode material more stable and uniform.

[0027] The surface of the high-nickel layered positive electrode material of the present invention is coated with a titanium oxide surface modification layer, which can effectively prevent the direct contact between the surface of the high-nickel layered positive electrode material and the electrolyte, reduce the side reaction between the electrode material and the electrolyte, prevent the electrolyte from penetrating into the interior of the secondary particles to cause microcracks, and maintain the structural stability of the positive electrode material during charging and discharging.

[0028] The lithium titanate coating formed by the surface residual alkali and titanium peroxide complex has almost no volume expansion during the charge and discharge process, which can alleviate the volume expansion of high-nickel materials during the charge and discharge process, thereby improving their long cycle performance and rate performance. In addition, the lithium titanate material has good electronic conductivity, which can greatly improve the conductivity of the positive electrode material.

[0029] By consuming the residual lithium on the surface of the positive electrode material and the titanium peroxide complex, a lithium titanate surface modification layer can be formed. The lithium titanate surface modification layer can effectively reduce the residual alkali content in the high-nickel positive electrode material, avoid the jelly phenomenon when the modified high-nickel positive electrode material is made into slurry, and further improve the electrochemical performance of the modified high-nickel positive electrode material. And improve the electronic conductivity and ion conductivity of the coating layer, thereby enhancing the stability of the electrode-electrolyte interface and reducing the charge transfer impedance of the battery during the charge and discharge process;

[0030] Therefore, the metal ions in the coating layer introduced into the subsurface of the high-nickel layered positive electrode material of the present invention can replace the original metal ions in the matrix material, which can improve the stability of the lattice oxygen structure, thereby improving the cycle performance and thermal stability of the material, and further improving the cycle life and safety performance of the lithium-ion battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is a SEM image of the high-nickel ternary positive electrode material prepared in Example 1 of the present invention;

[0032] Figure 2 This is the XRD pattern of the high nickel ternary positive electrode material prepared in Example 1 of the present invention;

[0033] Figure 3 This is an EDS image of the Ti element in the high-nickel ternary positive electrode material prepared in Example 1 of the present invention;

[0034] Figure 4 1 and 2. The long cycle curves of the high nickel ternary positive electrode material prepared in Example 1 of the present invention and the comparative example sample. DETAILED DESCRIPTION

[0035] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.

[0036] The ternary material LiNi in the following example 0.8 Co 0.1 Mn 0.1O2 can be made of commercially available materials in the prior art, or it can be made of the ternary material LiNi prepared in the following preparation example: 0.8 Co 0.1 Mn 0.1 O2.

[0037] The ternary material LiNi used in the following embodiments of the present invention is 0.8 Co 0.1 Mn 0.1 The preparation method of O2 comprises the following steps:

[0038] (1) nickel sulfate hexahydrate (NiSO4·6H2O), cobalt sulfate heptahydrate (CoSO4·7H2O) and manganese sulfate monohydrate (MnSO4·H2O) are weighed according to the required stoichiometric ratio and added to a mixed solution containing sodium hydroxide (NaOH) and ammonia water (NH3·H2O);

[0039] (2) controlling the temperature, pH value, stirring speed and other parameters of the mixed solution to obtain a preformed precipitate through reaction and aging;

[0040] (3) The precipitate obtained above was then washed with deionized water and dried overnight to finally obtain Ni 0.8 Co 0.1 Mn 0.1 (OH)2 precursor;

[0041] (4) Ni 0.8 Co 0.1 Mn 0.1 The (OH)2 precursor and LiOH·H2O were weighed in a molar ratio of 1:1.2 and mixed thoroughly by hand grinding in an agate mortar. The mixture was then heated at 500°C for 4 hours in an oxygen atmosphere in a tube furnace and then sintered at 800°C for 15 hours to obtain the ternary material LiNi 0.8 Co 0.1 Mn 0.1 O2(NCM811).

[0042] Example 1

[0043] The method for preparing the high-nickel ternary positive electrode material of this embodiment comprises the following steps:

[0044] 1) 67.4 mg of TiN nanopowder was added to 3.8 mL of deionized water and stirred evenly, and then 2.2 mL of hydrogen peroxide solution (mass fraction 30%) and 0.8 mL of ammonia solution (mass fraction 25%) were added to the mixed solution after stirring evenly; magnetic stirring was performed for 0.5 hours, and the mixed solution was gradually converted into a transparent yellow solution of titanium peroxide complex;

[0045] Adding a mixed solvent to the mixed solution, mixing evenly, to obtain a mixed solution; wherein the mixed solvent is a mixture of deionized water and ethanol, the volume of the deionized water is 50 mL, and the ethanol accounts for 70% of the volume of the mixed solvent;

[0046] 2) 49.9g of ternary material LiNi 0.8 Co 0.1 Mn 0.1 O2 (NCM811) is added to the mixed solution and mixed evenly; then the mixed solution is placed in an oven at 80°C for 30 hours to allow the peroxide titanium complex to nucleate and grow, and a loose yellow powder is obtained;

[0047] 3) The obtained yellow powder was annealed at 800° C. for 7 h in an argon atmosphere to form a titanium oxide surface modification layer of a certain thickness on the surface of the NCM811 powder.

[0048] Example 2

[0049] The method for preparing the high-nickel ternary positive electrode material of this embodiment comprises the following steps:

[0050] 1) 168.5 mg of TiN nanopowder was added to 9.4 mL of deionized water and stirred evenly, and then 5.4 mL of hydrogen peroxide solution (mass fraction 30%) and 2.0 mL of ammonia solution (mass fraction 25%) were added to the mixed solution after stirring evenly; the mixed solution was magnetically stirred for 0.5 hours, and the mixed solution was gradually converted into a transparent yellow solution of titanium peroxide complex;

[0051] Adding a mixed solvent to the mixed solution, mixing evenly, to obtain a mixed solution; wherein the mixed solvent is a mixture of deionized water and ethanol, the volume of the deionized water is 50 mL, and the ethanol accounts for 70% of the volume of the mixed solvent;

[0052] 2) 49.75g of ternary material LiNi 0.8 Co 0.1 Mn 0.1 O2 (NCM811) is added to the mixed solution and mixed evenly; then the mixed solution is placed in an oven at 80°C for 30 hours to allow the peroxide titanium complex to nucleate and grow, and a loose yellow powder is obtained;

[0053] 3) The obtained yellow powder was annealed at 800° C. for 7 h in an argon atmosphere to form a titanium oxide surface modification layer of a certain thickness on the surface of the NCM811 powder.

[0054] Example 3

[0055] The method for preparing the high-nickel ternary positive electrode material of this embodiment comprises the following steps:

[0056] 1) 336.9 mg of TiN nanopowder was added to 18.9 mL of deionized water and stirred evenly, and then 10.8 mL of hydrogen peroxide solution (mass fraction 30%) and 4.0 mL of ammonia solution (mass fraction 25%) were added to the mixed solution after stirring evenly; the mixed solution was magnetically stirred for 0.5 hours, and the mixed solution was gradually converted into a transparent yellow solution of titanium peroxide complex;

[0057] Adding a mixed solvent to the mixed solution, mixing evenly, to obtain a mixed solution; wherein the mixed solvent is a mixture of deionized water and ethanol, the volume of the deionized water is 50 mL, and the ethanol accounts for 70% of the volume of the mixed solvent;

[0058] 2) 49.5g of ternary material LiNi 0.8 Co 0.1 Mn 0.1 O2 (NCM811) is added to the mixed solution and mixed evenly; then the mixed solution is placed in an oven at 80°C for 30 hours to allow the peroxide titanium complex to nucleate and grow, and a loose yellow powder is obtained;

[0059] 3) The obtained yellow powder was annealed at 800° C. for 7 h in an argon atmosphere to form a titanium oxide surface modification layer of a certain thickness on the surface of the NCM811 powder.

[0060] Example 4

[0061] The method for preparing the high-nickel ternary positive electrode material of this embodiment comprises the following steps:

[0062] 1) Add 1.685 mg of TiN nanopowder to 94.3 mL of deionized water and stir evenly, then add 53.9 mL of hydrogen peroxide solution (mass fraction 30%) and 20.2 mL of ammonia solution (mass fraction 25%) to the mixed solution after stirring evenly; stir magnetically for 0.5 hour, and the mixed solution gradually transforms into a transparent yellow solution of titanium peroxide complex;

[0063] Adding a mixed solvent to the mixed solution, mixing evenly, to obtain a mixed solution; wherein the mixed solvent is a mixture of deionized water and ethanol, the volume of the deionized water is 50 mL, and the ethanol accounts for 70% of the volume of the mixed solvent;

[0064] 2) 47.5g of ternary material LiNi 0.8 Co 0.1 Mn 0.1 O2 (NCM811) is added to the mixed solution and mixed evenly; then the mixed solution is placed in an oven at 80°C for 30 hours to allow the peroxide titanium complex to nucleate and grow, and a loose yellow powder is obtained;

[0065] 3) The obtained yellow powder was annealed at 800° C. for 7 h in an argon atmosphere to form a titanium oxide surface modification layer of a certain thickness on the surface of the NCM811 powder.

[0066] Comparative Example

[0067] The untreated ternary material LiNi prepared by the present invention 0.8 Co 0.1 Mn 0.1 O2 (NCM811) was used as a comparative sample.

[0068] Experimental example

[0069] (1) Morphology test

[0070] The ternary material prepared in Example 1 was subjected to SEM and XRD tests, and the results were as follows: Figure 1 , Figure 2 shown.

[0071] from Figure 1 It can be seen that the positive electrode materials of the examples are all composed of secondary particles with a particle size of about 8 um formed by the agglomeration of primary particles, and the modification does not change the overall morphology of the positive electrode materials.

[0072] from Figure 2 From the element distribution diagram, it can be seen that the Ti element is evenly distributed on the surface of the high-nickel positive electrode material, and the coating layer formed is very uniform.

[0073] The ternary material of Example 1 was further subjected to EDS elemental analysis. Figure 3 This is the EDS graph of the Ti element in the positive electrode material prepared in Example 1.

[0074] from Figure 3 It can be seen that the positive electrode material modified with lithium titanate shows a typical hexagonal α-NaFeO2 structure, belonging to the R-3m space group, corresponding to the standard PDF card of high-nickel ternary materials (JCPDS#89-1979). In addition, the two pairs of split peaks (006) / (102) and (108) / (110) that are obviously split confirm that the material has a good degree of crystallinity and an ordered layered structure. The ratio of the (003) / (104) peak intensity represents the cation mixing degree of the material. The ratio of all samples is greater than 1.2, indicating a low degree of cation mixing. In addition, no peak position movement was observed in the enlarged spectrum of the (003) peak, which means that the titanium oxide surface modification layer coating only exists on the surface of the high-nickel NCM811 material and does not affect the internal crystal structure.

[0075] (2) Electrochemical performance test

[0076] The high-nickel ternary positive electrode material prepared in the above-mentioned Example 1 is used as a sample, and the sample is mixed evenly with polyvinylidene fluoride (PVDF), conductive carbon black, conductive carbon nanofiber (VGCF), and solvent N-methylpyrrolidone (NMP) to obtain a positive electrode slurry. The mass ratio of the sample to polyvinylidene fluoride (PVDF), conductive carbon black, and conductive carbon nanofiber (VGCF) is 90:5:2.5:2.5. The positive electrode slurry is coated on the surface of the positive electrode current collector, dried, and cut to make a positive electrode sheet. A lithium metal sheet is used as the negative electrode to assemble a lithium-ion battery. The capacity retention rate after 200 cycles was tested under the conditions of 1.0C (1C=200mA / g) and 3-4.3V. The results are as follows Figure 4 shown.

[0077] like Figure 4 As shown, the lithium ion battery prepared by the material of Example 1 has a capacity retention rate of 80.2% after 200 cycles. It can be seen that the material in the embodiment has significantly improved capacity retention rate and rate performance compared with comparative example 1, and has excellent electrochemical performance.

[0078] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A high-nickel ternary positive electrode material, characterized in that: It comprises a core and a coating layer, wherein the core is a ternary positive electrode material, and the coating layer comprises a titanium oxide compound.

2. The high-nickel ternary positive electrode material according to claim 1, characterized in that: The titanium oxide compound is TiO, TiO2, Ti2O3, Ti3O5, LiTiO2, Li2TiO3, Li4Ti5O 12 At least one of .

3. The high-nickel ternary positive electrode material according to claim 1, characterized in that: The mass of the coating layer accounts for 0.01%-10% of the sum of the mass of the core and the coating layer.

4. A method for preparing a high-nickel ternary positive electrode material, characterized in that: The steps include: 1) mixing a titanium source with hydrogen peroxide and ammonia in water to react to obtain a mixed reaction liquid; the titanium source is at least one of titanium propoxide, metatitanic acid, nano-titanium nitride, titanium tetrachloride, and tetrabutyl titanate; 2) uniformly mixing the mixed reaction liquid obtained in step 1) with a mixed solvent to obtain a mixed liquid; the mixed solvent is obtained by mixing ethanol and water; 3) adding the ternary positive electrode material to the mixed solution obtained in step 2), mixing evenly, and then treating at 25° C.-150° C. for 5-40 hours to obtain a powder; 4) The powder obtained in step 3) is kept at 300-1000° C. for 3-10 hours under an inert atmosphere to obtain the product.

5. The method for preparing a high-nickel ternary positive electrode material according to claim 4, characterized in that: The structural formula of the ternary cathode material in step 3) is LiNi x Co y Mn 1-x-y O2, 0.6≤x<1, 0 <y≤0.2,x+y<1。 6. The method for preparing a high-nickel ternary positive electrode material according to claim 5, characterized in that: The ternary positive electrode material is LiNi 0.6 Co 0.2 Mn 0.2 O2、LiNi 0.8 Co 0.1 Mn 0.1 O2 or LiNi 0.94 Co 0.03 Mn 0.03 O2.

7. The method for preparing a high-nickel ternary positive electrode material according to claim 4, characterized in that: The volume fraction of water in the mixed solvent in step 2) is 10%-50%.

8. The method for preparing a high-nickel ternary positive electrode material according to any one of claims 4 to 7, characterized in that: In step 1), the titanium source is mixed with hydrogen peroxide and ammonia in water to react by uniformly dispersing the titanium source in water, then adding hydrogen peroxide solution and ammonia solution, and mixing for 0.5-1h.

9. The method for preparing a high-nickel ternary positive electrode material according to claim 8, characterized in that: In step 1), 2-55 mL of hydrogen peroxide solution is used for every 67.4-1685 mg of titanium source; the mass fraction of the hydrogen peroxide solution is 30%.

10. A lithium ion battery comprising a positive electrode, a negative electrode, a separator, and an electrolyte; the positive electrode comprises a positive electrode current collector and a positive electrode material layer disposed on the positive electrode current collector, the positive electrode material layer comprises a positive electrode active material, characterized in that: The positive electrode active material is the high-nickel ternary positive electrode material described in claim 1 or the high-nickel ternary positive electrode material prepared by the preparation method according to claim 4.

Citation Information

Patent Citations

  • Preparation method of anode active material

    CN102169980A

  • Modified positive electrode material and preparation method and application thereof

    CN117691107A

  • Aluminum-doped lithium titanate coated ternary positive electrode material as well as preparation method and application thereof

    CN119080083A

  • Positive electrode active material for lithium secondary batteries, electrode for lithium secondary batteries, and lithium secondary battery

    JP2015099646A

  • Processes for forming doped-metal oxides thin films on electrode for interphase control

    US20230343935A1